A Clinical Study of the Use of Savary‑Gilliard Dilators in Corrosive Esophageal Strictures without the Use of Fluoroscopy: A Reality in Resource‑Limited Settings in a Developing Country - Bhatt, Varsha Rajat; Kakrani, Arjun Lal (Journal of Digestive Endoscopy, 2018)
Context: Corrosive compounds are either acids or alkalis, and their ingestion can cause esophageal strictures which may be tortuous and multiple. Aims: The aim of study was to assess therapeutic efficacy and safety of dilatation using Savary‑Gilliard dilators in these patients without the use of fluoroscopy. Settings and Design: A cross‑sectional observational study, conducted for 18 months in a tertiary care teaching hospital in Western India. Subjects and Methods: Ten dysphagic patients who had a history of corrosive ingestion 2 months or more before presentation, who had documented esophageal strictures on endoscopy were included. Barium swallow and endoscopy confirmed the site, length, and number of strictures. Dilatation with Savary‑Gilliard dilators was done without the use of fluoroscopy with the help of guide wire in “rule of threes.” Patients were followed up immediately and for 12 months. Descriptive statistics, mean, and SD were applied in EPI info version 7 software. Results: The mean age of 29 + 6.5 years and 70% were females. About 80% had dysphagia Grades III and IV. On endoscopy, 40% had strictures at multiple sites and 60% of patients had strictures more than 5 cm in length. 50% strictures were very tight. Number of patients in whom there was the passage of one dilator more than the stricture in the first session were 80%. A mean of 8.28 sessions of dilatation were required. Adequate dysphagia relief was achieved in 8 (80%) patients, while there were 2 failures. A total of 180 dilatations were performed on these 10 patients of corrosive strictures over a period of 12 months. One minor perforation occurred in this study. Conclusions: In resource‑limited settings such as India, dilatation without fluoroscopy can be considered as effective and safe initial management for corrosive strictures.
Keywords: Corrosive; esophageal; fluoroscopy; Savary‑Gilliard dilators; stricture